CLINICAL PROFILE OF TYPE-1 DIABETES PEDIATRIC PATIENTS IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL SURABAYA: CORRELATION OF GROWTH STATUS AND METABOLIC CONTROL - Muhammad Faizi; Mia Ratwita Andarsini; Grawira Drana Putra Respati; Agung Pranoto (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights1. Diabetes mellitus type 1 (DM) is a chronic autoimmune illness characterized by insulin insufficiency and hyperglycemia as a consequence.2. Stable HbA1c levels may be indicative of improved growth rates. AbstractBackground: Type-1 diabetes mellitus (DM) is a chronic auto-immune disease characterized by insulin insufficiency and resultant hyperglycemia caused by the destruction of insulin-producing beta cells in the pancreas. Metabolic control in type-1 DM affects the metabolism of patients, one of which is growth status, which is influenced by growth hormone. Improved growth rates can indicate stable HbA1c levels. However, whether growth is affected by the degree of diabetic control is still debatable. Objective: This study was conducted to determine whether the metabolic control correlates with growth status of children with type-1 diabetes in the Endocrine Polyclinic at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Material and Method: Retrospective observational analysis with a cross-sectional method was conducted on 96 type-1 DM patients at Dr. Soetomo General Academic Hospital Surabaya, Indonesia. The analysis was carried out using Chi-Square test to determine whether there was a correlation. Result: From a total of 96 pediatric patients, the majority was male (54.1%), patients with high-risk metabolic control were 79.2%, and those with z-score normal category were 62.5%. The results indicated no significant correlation between growth status and metabolic control of pediatric patients, with Chi-Square test results showed p=0.421 (p>0.05). Conclusion: There was no significant correlation between growth status and metabolic control of type-1 diabetes pediatric patients at the Endocrine Polyclinic Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.